2017
DOI: 10.1152/ajplung.00510.2016
|View full text |Cite
|
Sign up to set email alerts
|

Autophagy plays a role in FSTL1-induced epithelial mesenchymal transition and airway remodeling in asthma

Abstract: Asthma is a chronic disease related to airway hyperresponsiveness and airway remodeling. Airway remodeling is the important reason of refractory asthma and is associated with differentiation of airway epithelia into myofibroblasts via epithelial-mesenchymal transition (EMT) to increase the process of subepithelial fibrosis. There is growing evidence that autophagy modulates remodeling. However, the underlying molecular mechanisms of these effects are still unclear. In this study, we hypothesized that Follistat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
69
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 82 publications
(72 citation statements)
references
References 45 publications
3
69
0
Order By: Relevance
“…It has been reported that the autophagic markers including LC3, Atg 5, and/or Beclin 1 were upregulated in the airway of both patients with asthma and OVA‐challenged mice (T. Liu et al, ). By double staining the mouse lung tissues with LC3B and α‐SMA antibodies, we further noted that the expression of LC3B was markedly upregulated in these α‐SMA‐positive cells in asthmatic mice.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…It has been reported that the autophagic markers including LC3, Atg 5, and/or Beclin 1 were upregulated in the airway of both patients with asthma and OVA‐challenged mice (T. Liu et al, ). By double staining the mouse lung tissues with LC3B and α‐SMA antibodies, we further noted that the expression of LC3B was markedly upregulated in these α‐SMA‐positive cells in asthmatic mice.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to alleviating airway inflammation and remodeling, CHR also inhibited autophagy: LC3, Atg 5, and Beclin 1 were decreased. Because inhibition OVA‐induced autophagy can mitigate asthmatic inflammation and airway remodeling (T. Liu et al, ), it is plausible to propose that autophagy inhibition is involved in the antiasthmatic effects of CHR.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…International Publisher including breast cancer, glioblastoma, hepatocellular carcinoma, and et al [9][10][11]. However, the biological role and clinical significance of miR-144-3p in OSCC are still not known.…”
Section: Ivyspringmentioning
confidence: 99%
“…A cycle of persistent airway epithelial damage, improper repair and hyperactive epithelial–mesenchymal transition (EMT) in bronchial epithelial cells has been previously reported to contribute to the pathogenesis of airway inflammation and airway remodelling, which are thought to be the key factors most closely associated with the incidence and prognosis of asthma. In some cases of asthma, the bronchial epithelial cells may undergo EMT and play a pivotal role in subepithelial myofibroblast recruitment and airway inflammation (Hackett et al., , ; Heijink, Postma, Noordhoek, Broekema, & Kapus, ; Liu et al., ). Therefore, clarifying the events of EMT in bronchial epithelial cells in response to harmful stresses may provide insights for improving therapeutic options for asthma.…”
Section: Introductionmentioning
confidence: 99%